Immunolocalization of Lipoxygenase in the Anther Wall Cells of Lathyrus undulatus Boiss. during Programmed Cell Death - (:unkn) unknown (My University, 2011)
Lipoxygenase catalyzes oxygenation of long chain fatty acids to hydroperoxides and is involved in the degradation of membranes occuring in some types of programmed cell death (PCD). The localization of lipoxygenase in the anther wall layers of L. undulatus during cellular degradation was analyzed by immunogold labeling technique at young and vacuolated pollen stage, due to the close relation between lipoxygenase activity and membrane degradation in programmed cell death. Immunoreaction to lipoxygenase was monitored slightly at young pollen stage in the anther wall cells. As programmed cell death signals progress, lipoxygenase revealed in anther wall cells intensely. At vacuolated pollen stage tapetal cells came forward with ultrastructural changes such as cell, organelle and membrane disintegration. At the indicated stage immunogold particles indicating sites of LOX PAb-binding epitopes were located in the nucleus (chromatin was condensed and lined at the periphery), cytoplasm and close to long dilated rough endoplasmic reticulum (RER) cisterna. In conclusion lipoxygenase increase which has a role in the membrane degeneration, possibly induced the collapse of tonoplast, nuclear and plasma membrane and triggered programmed cell death in the tapetal cells of L. undulatus as well as the other wall cells.